Ocular Trauma Management in Industrial Workers at Primary Care Services: A Systematic Review of Randomized Controlled Trials and Primary Studies - Sri Adinda Ayu; Kuwati (The Indonesian Journal of General Medicine, 2026)
Introduction: Ocular trauma in industrial workers represents a significant global public health burden, with primary care services serving as the first point of contact. However, standardization of management at this level remains variable and incompletely characterized. This systematic review aims to evaluate the effectiveness of ocular trauma management interventions delivered at primary care settings for industrial workers. Methods: A comprehensive literature search adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Studies were included if they involved adult industrial workers, reported ocular trauma management interventions at primary or emergency care level, and provided quantifiable outcomes. Risk of bias was assessed using the Cochrane Risk of Bias Tool 2.0 (RoB 2) for RCTs and the Newcastle-Ottawa Scale (NOS) for observational studies. Results: Eighteen studies comprising 14,327 participants met the inclusion criteria. Eye patching for simple corneal abrasions conferred no significant benefit over no-patch management (RR 0.89, 95% CI 0.79–1.00). Topical NSAIDs (ketorolac 0.5%, diclofenac 0.1%) significantly reduced pain and supplemental analgesic requirements (p<0.002). Immediate and prolonged copious irrigation (≥1 liter saline, 30–60 minutes) for chemical eye burns significantly improved visual outcomes. Enhanced educational interventions increased protective eyewear compliance by 16% versus standard education (95% CI 3–29%). Non-use of protective eyewear was documented in 78–89% of injured workers. Discussion: The evidence demonstrates that eye patching lacks benefit for simple corneal abrasions, topical NSAIDs represent the most evidence-supported analgesia, and immediate irrigation is critical for chemical injuries. Protective eyewear compliance remains critically low, with multicomponent educational programs showing the most promise. Conclusion: Key priorities include abandoning routine eye patching, adopting topical NSAID analgesia, implementing immediate chemical irrigation protocols, and sustaining multicomponent programs to improve protective eyewear compliance.